Political connections and firm pollution behaviour: An empirical study - Yuping Deng; Yanrui Wu; Helian Xu (Bank of Finland, Institute for Economies in Transition (BOFIT), 2019)
A firm's top manager and a government official may be connected due to special circumstances. This social relationship or political connection may provide industrial polluters with protection or a "pollution shelter" which could lead to severe environmental deterioration. This paper aims to examine the link between political connections and firms' pollution discharges by using Chinese data. Empirical results show that political connections are the institutional origin for firms to adopt strategic pollution discharges. Government officials who are young, of low education, promoted locally and in office for a relatively long time are more likely to build political connections with polluters. This phenomenon results in inadequate enforcement of regulation and emission control. The pollution discharges of politically connected firms also vary considerably due to firm heterogeneity. This study also shows that pollution shelter effects caused by political connections are more obvious in the central and western regions, prefecture cities and capital-intensive industries.
URN:NBN:fi:bof-201902281073
Keywords: Q51; L20; O12; 330; political connections; pollution discharges; political promotion; China